Electrochemical Studies of Cadmium(II) Complexes with Itaconic Acid in Non-Aqueous Media at Dropping Mercury Electrode - KARADIA, CHANCHAL; SHARMA, SUNITA; GUPTA*, O.D. (Asian Journal of Chemistry, 2009)
Studies of Cd(II) complexes with itaconic acid have been carried out by polarographic method in non-aqueous (40 % DMSO, 40 % DMF and 40 % ethanol) medium under varying temperatures, at 298 and 308 K in presence of potassium chloride as a supporting electrolyte. The reduction of Cd(II) was found to be reversible in non-aqueous medium for itaconic acid ligand and have shown the formation of 1:1, 1:2 and 1:3 complexes. DeFord and Hume's method as modified by Irving has been applied for the determination of composition and stability constant of the complexes species. The changes in thermodynamic parameters ΔH°, ΔG° and ΔS° accompanying complexation have been evaluated. The mathematical Mihailov's method has also been applied for the compa-rison of stability constants values.